Study on authority watermark of the electronic chart based on the semantics characteristics - Ming-zhu LAI; Li-guo ZHANG; Wei-miao FENG; Yuan-yuan WANG; Yong WANG; Shou-zheng LI (Tongxin xuebao)
In order to expand the function of watermarking technology, a concept of authority watermark, for which, wa-termarks defining the users' specific operations on the digital carriers was proposed. With interception technology on im-ages, the constructed authority watermark based on the semantics characteristics of the watermark images, through the interpretation of the watermarks, accessing behaviors on the electronic chart would be controlled. Experimental results show that, this method can realize safety distribution and operation verification under the network environment, espe-cially with outstanding performance in tamper resistant and forgery.